Distribution extension of Escherbothrium molinae Berman and Brooks, 1994 (Cestoda: Tetraphyllidea: Triloculariidae) in Urotrygon sp. from the Pacific Coast of Mexico - Francisco Zaragoza-Tapia; Scott Monks; Griselda Pulido-Flores; Juan Violante-González (Check List, 2013)
Cestodes collected from the spiral valves of the stingray Urotrygon sp. from the Pacific coast of Mexico were identified as Escherbothrium molinae Berman and Brooks, 1994. The first report of the species was from the Gulf of Nicoya and the Guanacaste coast, Costa Rica; this work represents the second report of the species since the original description and extends its distribution north to Acapulco, Guerrero, Mexico.